2007
DOI: 10.1007/s00264-007-0423-9
|View full text |Cite
|
Sign up to set email alerts
|

OP-1/BMP-7 in cartilage repair

Abstract: Three years ago we published a book chapter on the role of bone morphogenetic proteins (BMPs) in cartilage repair. Since that time our understanding of the function of osteogenic protein-1 (OP-1) or BMP-7 in cartilage homeostasis and repair has substantially improved and therefore we decided to devote a current review solely to this BMP. Here we summarise the information accumulated on OP-1 from in vitro and ex vivo studies with cartilage cells and tissues as well as from in vivo studies of cartilage repair in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
154
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 189 publications
(165 citation statements)
references
References 43 publications
(73 reference statements)
5
154
0
4
Order By: Relevance
“…Col 2-3/4C short is a collagen fragment resulting from metalloproteinase degradation of hyaline cartilage collagen, and suppression of this marker indicates that catabolic metabolism was blocked to some degree. These data are consistent with other experiments that showed BMP-7 increased the survival and anabolic capacity of normal and OA chondrocytes in the face of signaling molecules that promote catabolic chondrocyte metabolism and OA degeneration 15,17,18,42,46,47 This protective effect is partly mediated by an increase in endogenous BMP-7 production in cartilage, synovial membrane, and other tissues. Taken together with previous in vitro data recently reviewed, 42 this is more evidence that BMP-7 can initiate an effective protective response that may also induce some degree of intrinsic repair.…”
Section: Bmp-7 Protects Against Progression Of Cartilage Degenerationsupporting
confidence: 81%
See 1 more Smart Citation
“…Col 2-3/4C short is a collagen fragment resulting from metalloproteinase degradation of hyaline cartilage collagen, and suppression of this marker indicates that catabolic metabolism was blocked to some degree. These data are consistent with other experiments that showed BMP-7 increased the survival and anabolic capacity of normal and OA chondrocytes in the face of signaling molecules that promote catabolic chondrocyte metabolism and OA degeneration 15,17,18,42,46,47 This protective effect is partly mediated by an increase in endogenous BMP-7 production in cartilage, synovial membrane, and other tissues. Taken together with previous in vitro data recently reviewed, 42 this is more evidence that BMP-7 can initiate an effective protective response that may also induce some degree of intrinsic repair.…”
Section: Bmp-7 Protects Against Progression Of Cartilage Degenerationsupporting
confidence: 81%
“…Gene expression studies in BMP-7-treated cartilage have shown that production of this enzyme was suppressed. 42 In animals from group A caspase-3 staining was confined to the superficial zone in BMP-7-treated joints, and was frequently absent despite abnormal cartilage morphology present at the injury site. By contrast, vehicle-treated joints had caspase-3-positive cells throughout the femoral condyle articular surface in sites distant from the original injury.…”
mentioning
confidence: 99%
“…4 Among BMPs, BMP-7 is especially attractive, because it is one of two BMPs already approved for clinical use in various applications by the FDA. Recent data from an anterior cruciate ligament transection model in rabbits demonstrated that continuous intraarticular infusion of BMP-7 had a protective effect on cartilage degeneration, 5 suggesting the possible utility of BMP-7 as a treatment for human OA patients.…”
mentioning
confidence: 99%
“…IGF-1 FGF-18 (Hunter et al, 2010); (Hayashi et al, 2008(Hayashi et al, , 2010; (Hurtig et al, 2009); (Chubinskaya et al, 2007); (Cook et al, 2003); (Badlani et al, 2008) ; (Fortier et al, 2002); (Im et al, 2003) (Moore et al, 2005); (Lotz & Kraus, 2010); (Ellsworth et al, 2002) (Ewers et al,2002(Ewers et al, ,2000bNewberry et al,1997;Oegema et al,1993;Thompson et al,1991). In the canine model, cell death and fractures in the subchondral bone and calcified cartilage were observed without full-thickness cracks in the cartilage.…”
Section: Mmp Inhibitors / Timpsmentioning
confidence: 99%